Justification of Lack of Obligation of Institutionalising Social Phenomena Based on the Example of Bills Regarding Partnerships - Michałowska, Kinga (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article contains considerations on establishing premises justifying the launching of legislative actions concerning new social phenomena. Research has been done in two areas – one to establish the general basis for legislative action, and the other to specify the general considerations in the absence of the need for institutionalisation, especially in partnerships and their legal consequences stemming from legal regulations in terms of internal and external law.